Long-Term Cognitive Impairment Associated With Delirium in Acute Neurological Injury - Meeks, Jennifer R; Bambhroliya, Arvind B; Sheth, Sunil A; Khan, Babar; Slooter, Arjen J C; Ely, E Wesley; Miller, Charles C; Tyson, Jon E; McCullough, Louise D; Savitz, Sean I; Vahidy, Farhaan S (Lippincott Williams & Wilkins, 2020)
Objectives: To characterize the risk of long-term cognitive impairment associated with delirium in acute neurologic injury patients. Design: We analyzed a 10-year cohort of adult acute neurologic injury patients (stroke and traumatic brain injury) without preexisting mild cognitive impairment or dementia, utilizing administrative databases. Patients were followed for in-hospital delirium and mild cognitive impairment or dementia. We report incidence and adjusted hazard ratios for mild cognitive impairment or dementia associated with delirium. Subgroups analyzed include acute neurologic injury categories, dementia subtypes, repeated delirium exposure, and age strata. Setting: We used state emergency department and state inpatient databases for New York, Florida, and California. All visits are included in the databases regardless of payer status. Patients: We included adult patients with diagnosis of stroke and traumatic brain injury as acute neurologic injury. Patients with preexisting mild cognitive impairment or dementia were excluded. Interventions: None. Measurements and Main Results: Among 911,380 acute neurologic injury patients, 5.2% were diagnosed with delirium. Mild cognitive impairment or dementia incidence among delirium patients was approximately twice that of nondelirium patients. In adjusted models, risk of mild cognitive impairment or dementia was higher among patients with delirium (adjusted hazard ratio, 1.58). Increased risk was observed across all subgroups including patients less than or equal to 55 years old. Conclusions: Identification, management, and prevention of in-hospital delirium could potentially improve long-term cognitive outcomes in acute neurologic injury patients.
Keywords: Journal Article